Soil pH, Soil Organic Matter, and Crop Yields in Winter Wheat–Summer Fallow Systems. (1st March 2017) - Ghimire, Rajan; Machado, Stephen; Bista, Prakriti
Abstract : Core Ideas: Continuous addition of ammonical N fertilizer increases soil acidity. Soil acidification influences nutrient dynamics and crop yields. Soil organic C and soil N decreased over years under winter wheat–summer fallow system. Soil acidifcation was not related with soil organic carbon and soil N loss over years. Soil acidification should be carefully monitored in systems using ammonical N fertilizers. Soil acidification has become a major environmental challenge for crop production in the inland Pacific Northwest (iPNW). We evaluated the effects of tillage and N‐fertilizer management on soil pH, soil organic carbon (SOC), soil N, and crop yields from 1995 through 2010 in an ongoing long‐term experiment in eastern Oregon. Tillage systems included moldboard plow (MP), disk plow (DP), and subsurface sweep (SW) and N‐fertilizer rates were 0, 45, 90, 135, 180 kg N ha −1 crop −1 in a dryland winter wheat ( Triticum aestivum L.)–summer fallow (WW–SF) system. Soil pH, SOC, and N were monitored in 1995 and 2010, and crop yields were monitored every other year. Soil pH was lower in the higher N rate treatments. Long‐term N fertilizer application increased soil acidity in 0‐ to 10‐cm depth by 0.3, 0.2, and 0.3 units in MP, DP, and SW, respectively, for every 1000 kg N applied through ammonical N fertilizers. Soil pH was higher in DP than MP in 10‐ to 20‐ and 20‐ to 30‐cm depth profiles. The SOC and N concentrations in the top 30‐cm depth were lower in 2010 than in 1995 across all treatments. Wheat yield increased significantly with increase in N rates from 0 to 90 kg N ha −1 crop −1 . There were no further yield increases above 90 kg N ha −1 crop −1 . Soil acidification, SOC and nutrient dynamics should be carefully monitored in cropping systems using ammonical N fertilizers, particularly under high rate of N application and reduced tillage.